ADR AND CIVIL PROCEEDING IN ITALY 2021, POTENTIAL DEVELOPMENTS COMMISSIONE LUISO - Matteucci, Giovanni (Revista Eletrônica de Direito Processual, 2021)
Italy aims to reduce the length of civil trials. In 2021 the government has appointed the Commissione Luiso, which -with regard to out-of-court methods of dispute resolution- recommends tax incentives, increase of matters subject to mandatory mediation, enhancement of court-appointed-mediation, clarification of the mediation proceeding requirements to make it more effective, involvement of the public administration, quality of training.